Transcriptomic comparison of corneal endothelial cells in young versus old corneas - Jin Sun Hwang; Je Hyun Seo; Hyeon Jung Kim; Yunkyoung Ryu; Young Lee; Young Joo Shin (Scientific Reports)
Abstract Corneal endothelial cells, situated on the innermost layer of the cornea, are vital for maintaining its clarity and thickness by regulating fluid. In this study, we investigated the differences in the transcriptome between young and old corneal endothelial cells using next-generation sequencing (NGS). Cultured endothelial cells from both young and elderly donors were subjected to NGS to unravel the transcriptomic landscape. Subsequent analyses, facilitated by Metascape, allowed for the dissection of gene expression variances, unearthing pivotal biological pathways. A total of 568 genes showed differences, and were related to Endomembrane system organization, nuclear receptors meta pathway, efferocytosis, etc. Notably, a reduction in the expression of 260 genes was observed in the aged cells form old donors, and in the related analysis, eukaryotic translation initiation, integrator complex, and Hippo YAP signaling were significant. Conversely, 308 genes exhibited elevated expression levels in the elderly, correlating with processes including transition metal ion transport and glycoprotein biosynthesis. In conclusion, our investigation has revealed critical genes involved in the aging process of corneal endothelial cells and elucidated their underlying biological pathways. These insights are instrumental in selecting targets for therapeutic intervention, thereby facilitating the advancement of novel therapeutic approaches for the restoration and preservation of corneal endothelial cell function.